Dramatic impact of the TiO2 polymorph on the electrical properties of 'stoichiometric' Na0.5Bi0.5TiO3 ceramics prepared by solid-state reaction. Issue 2 (20th December 2021) - Yang, Fan; Hu, Yidong; Hu, Qiaodan; Steiner, Sebastian; Frömling, Till; Li, Linhao; Wu, Patrick; Pradal-Velázquez, Emilio; Sinclair, Derek C.
Abstract : The TiO2 polymorph has a dramatic impact on the electrical conductivity and conduction mechanisms of nominally stoichiometric NBT ceramics prepared by solid-state reaction. Abstract : Bulk conductivity ( σ b ) values of nominally stoichiometric Na0.5 Bi0.5 TiO3 (NBT) prepared by solid-state reaction collated from literature show random variation between 10 −6 to 10 −3 S cm −1 (at 600 °C). This makes it challenging to obtain reliable and reproducible performances of NBT-based devices, especially as the underlying reason(s) for this variance are not fully understood. Here we report the dramatic impact of the TiO2 reagent, in particular, the polymorphic form of TiO2 on the electrical conductivity and conduction mechanism of NBT. Based on our solid-state processing route, NBT ceramics prepared by rutile TiO2 are ionically conductive, and those prepared by anatase TiO2 are insulating. The dramatic difference in electrical properties of NBT prepared using rutile and anatase TiO2 is related to the NBT formation process: the intermediate phase Bi12 TiO20 is more stable during formation of NBT in the case of anatase TiO2, which reduces the volatility of Bi2 O3 during solid-state reaction. These results give plausible explanations for the large variation of σ b reported in the literature and highlight the importance of selecting an appropriate TiO2 reagent when targeting controllable σ b in NBT-based ceramics. For ion-conducting applications (such as in intermediate-temperature solid oxide fuel cells, IT-SOFCs), rutile TiO2 should be used, and for dielectric applications (such as in multilayer ceramic capacitors, MLCC) anatase TiO2 should be used.